Acceptance of technology amongst oil palm smallholders / Muhsien Badrul Isham - Muhsien Badrul Isham (Faculty of Plantation and Agrotechnology, 2016)
Technology has become important part of today's life. Therefore, many oil palm smallholders implement technology in their farm for various reasons to enhance production of fresh fruit bunch (FFB). Despite of the advancement and variety of available of equipment, there is an eminent need to investigate and verify the current position of the acceptance of those technologies that are available to smooth the plantation operation and increase production of FFB among smallholder. Therefore, in this study, Technology Acceptance Model (TAM) used to study the oil palm smallholder acceptance of technology within oil palm industry. A sample of 108 oil palm smallholders took part in the research. The purpose of this study is to design a quantitative approach based on the technology acceptance questionnaire as its primary research methodology. The related elements for evaluation included: Perceived of Usefulness, Perceived Ease of Use, Self-satisfaction and Attitude. All these elements are modified to suit the context of study. Furthermore, this study outlines the details of each element and its relevance toward the research issue. The outcome of the study represents series of approaches that will apply for checking the suitability of a technology on oil palm smallholder for oil palm industry and how well it achieves the aims and objectives of the design.